Cross-Cultural Adaptation and Psychometric Evaluation of the Job Satisfaction Scale in Indonesia - Abdul Rahman Ibrahim; Fattah Hanurawan; Isfridus Tafin Tnopo; Puput Anis Biantoro; Sirilus Ugi Daeng; Cica Aprilia Munika (Universitas Muhammadiyah Metro, 2025)
This study aimed to adapt and validate the Job Satisfaction Scale (JSS) developed by Ã‡alÄ±ÅŸkan and KÃ¶roÄŸlu (2024) into the Indonesian context. The adaptation followed the International Test Commission (ITC) guidelines through forward–backward translation, expert review, and readability testing. The study involved 250 employees from public and private sectors across Indonesia using a quantitative ex post facto design. Data were analyzed using Cronbach’s alpha and Confirmatory Factor Analysis (CFA). The results showed high internal consistency for the overall scale (Î± = .956), with Internal Satisfaction (Î± = .901) and External Satisfaction (Î± = .925) demonstrating strong reliability. The CFA model indicated excellent fit indices (CFI = .999; RMSEA = .025), confirming the two-factor structure of the scale. These findings suggest that the Indonesian version of the JSS is a psychometrically valid and reliable instrument for assessing job satisfaction among Indonesian employees. Future studies are recommended to examine its measurement invariance across occupational and regional groups to strengthen its generalizability.